Lyophilized and gamma-sterilized allogeneic bone implant used as a spacer for advancement of a modified tibial tuberosity in the treatment of cranial cruciate ligament disease in dogs - Morato, Glaucia O.; Rocha, Artur G.; Chung, Denise G.; Conceicao, Maria E. B. A. M. da [UNESP]; Minto, Bruno W. [UNESP]; Padilha Filho, Joao G. [UNESP]; Dias, Luis G. G. G. [UNESP] (Public Library Science, 2019)
The objective of this study was to evaluate the use of a lyophilized and gamma-sterilized allogeneic freeze-dried bone wedge as a spacer for advancement of a modified tibial tuberosity (mTTA) in 16 knees that were clinically diagnosed with cranial cruciate ligament disease. Patients underwent radiography before the surgical procedure as well as immediately after surgery and at 30, 60, 90 and 120 days post-surgery, and their locomotion was evaluated at the same time points except for the immediate postoperative period. The surgical wounds were evaluated for signs of infection and rejection of the bone implant. Locomotion was graded on a scale of 0-5, with 0 indicating no limping and 5 indicating limb functional impotence. The tibial-tibial bone-tibial implant interfaces were evaluated radiographically, and each interface was assigned scores of 0-3, with 0 indicating no contact between the implant and adjacent bone and 3 indicating a bone bridge throughout the interface. The patients showed good clinical and radiographic recovery. The lyophilized bone spacer allowed for easy storage and transport and rapid and satisfactory execution of mTTA while showing resistance to drilling and fixation with screws in 87.5% of cases and a mean surgical time of 45.9 minutes. No immunogenic reactions were observed in 93.7% of the cases. One patient presented infection of the surgical focus, which showed remission after antimicrobial therapy. All patients showed functional recovery of the operated limb, with the number of clinically healthy patients being higher than those with claudication at 120 days (p <= 0.05). In all patients, it was possible to verify the incorporation of the bone implant into the tibia. Bone union occurred progressively, and the degrees of bone union observed on radiographs at postoperative days 60, 90, and 120 were significantly greater (p < 0.05) than those observed in the immediate postoperative period and at 30 days.